UNDERSTANDING THE MECHANISM OF HYPOXIA TOLERANCE IN RICE - Oppong, G.K. (2024)
Rice (Oryza sativa) is an important food security crop, serving as a staple food for more than half of the global population. Due to rising labour costs and water scarcity, many farmers in sub-tropical and tropical regions are adopting direct seeded rice over the traditional method of transplanting. However, a major bottleneck to the widespread adoption of this approach is poor germination and seedling establishment, especially in flood prone areas. This is because most elite rice varieties are sensitive to anaerobic germination (AG). To elucidate the mechanisms underpinning AG, which are poorly understood, this thesis employed a multi-omic approach to compare AG tolerant and sensitive rice. Development of an automated time lapse phenotyping platform clearly indicated different rates of growth and development between tolerant and sensitive varieties germinating under submergence in darkness and in a day/night cycle. To identify genes and proteins important for AG tolerance, a tolerant landrace, Ma-Zhan Red, was compared with a sensitive, elite variety, IR64, using transcriptomic and quantitative proteomic analysis of embryos and coleoptiles. Although many genes and proteins were similarly regulated by hypoxia in the tolerant and sensitive variety, weighted gene correlation network analysis identified genes that were uniquely up-regulated under AG in Ma-Zhan Red and co-regulated with known AG-causative genes, Trehalose phosphate phosphatase 7 (Os09g0369400) and B12D family protein (Os07g0604700). Four genes: SAUR10, (Os02g0512000), Haem peroxidase (Os07g0104500), PIK6 (Os11g0689100), and CIPK04 (Os12g0603700) had not previously been associated with AG and were selected for further study. Their putative roles in tolerance were tested by over-expression in AG sensitive backgrounds. AG assays conducted on the T1 segregating population of the overexpression lines of CIPK04 and SAUR10 provided preliminary evidence of the potential role of these genes in AG tolerance. The combined transcriptome/proteome analysis also identified proteins including alcohol dehydrogenase 2 and aquaporins whose abundance increased under AG in Ma-Zhan Red without a corresponding change in transcript, indicating the importance of post-transcriptional regulation under AG conditions. The identification and functional validation of these genes and proteins opens new avenues for future research and potential applications in crop improvement through conventional breeding.